Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1987
DOI: 10.4039/ent119985-11
|View full text |Cite
|
Sign up to set email alerts
|

REPRODUCTION AND DEVELOPMENT OF THE EASTERN LARCH BEETLE, DENDROCTONUS SIMPLEX LECONTE (COLEOPTERA: SCOLYTIDAE), IN NEWFOUNDLAND

Abstract: Overwintered adults of Dendroctorms simplex LeConte emerged in May and June and produced one generation and two broods in 1983 and 1984. Egg galleries were vertical, slightly sinuous, and significantly longer in first brood trees than in second brood trees . Females laid zero to four eggs per niche . The average number of eggs per gallery was significantly higher in first brood trees (48) than in second brood trees (31). Mean number of eggs per centimetre of gallery was 1.2 for both broods. Mean brood density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
2

Year Published

1988
1988
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 12 publications
(22 reference statements)
3
54
2
Order By: Relevance
“…The bars representing the same type of muscle that have the same letter are not signiÞcantly different (Tukey, P Ͻ 0.05). ßight muscles has also been reported in other insect species, particularly Scolytinae beetles, during the egg gallery construction and oviposition (Chapman 1956, Atkins and Farris 1962, Langor 1987. Before reemergence, beetles of some species have the ability to regenerate ßight muscles (Langor 1987, Tanaka 2000 but the coffee berry borer apparently does not (Ticheler 1961).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The bars representing the same type of muscle that have the same letter are not signiÞcantly different (Tukey, P Ͻ 0.05). ßight muscles has also been reported in other insect species, particularly Scolytinae beetles, during the egg gallery construction and oviposition (Chapman 1956, Atkins and Farris 1962, Langor 1987. Before reemergence, beetles of some species have the ability to regenerate ßight muscles (Langor 1987, Tanaka 2000 but the coffee berry borer apparently does not (Ticheler 1961).…”
Section: Discussionmentioning
confidence: 90%
“…Degeneration of coffee berry borer ßight muscles has been reported, but apparently the beetle is not able to regenerate them (Ticheler 1961). In other Scolytinae, the ßight muscles of beetles degenerate and regenerate following gallery initiation (Chapman 1956, Borden and Slater 1969, Langor 1987, Robertson 1998. The ßight muscles of H. hampei females degenerate only after fecundation (Ticheler 1961).…”
mentioning
confidence: 98%
“…For example, Dendroctonus frontalis Zimmermann, D. bre6icomis, D. rufipennis, D. ponderosae, and I. typographus, five of the most damaging pests in North America and Europe (Knight et al 1956;Miller & Keen 1960;Coulson 1979;Christiansen 1985a,b;Reynolds & Hard 1991), yielded the highest optimal attack densities. In contrast, Scolytus 6entralis LeConte and Dendroctonus simplex LeConte kill fewer trees annually than the above species, rarely undergo widespread outbreaks, and are almost always associated with severely stressed trees (Berryman 1973;Werner 1986;Langor & Raske 1989;Ferrell et al 1994), and showed much lower optimal colonization rates. This pattern may prove useful in analyzing bark beetle ecology and behavior.…”
Section: Does Individual Bark Beetle Fitness Benefit From Colonial Brmentioning
confidence: 99%
“…Sporadic tree mortality caused by ELB has been recorded in all other provinces and territories in the last 40 years (see Langor and Raske 1988), but the outbreak in eastern North America in the 1970's and 1980's did not spread west of Quebec In the mid-1960's, a small outbreak occurred in Manitoba but was short-lived and localized (Drouin and Turnock 1967) Maine, New Hampshire, Vermont and New York Tree mortality by the ELB, concurrent with that in Atlantic Canada, was recorded in Maine, New Hampshire, Vermont and New York (Fig. 1).…”
Section: Other Provinces and Territoriesmentioning
confidence: 99%